SAT-LB044 HCG as a Predictor of Pregnancy Evolution in Patients Undergoing IVF - Decia, Magdalena (J Endocr Soc, 2019)
Human chorionic gonadotropin (hCG) levels in early pregnancy are predictive for pregnancy outcome after an embryo transfer (ET), however prognostic values are not consistent due to the different timing of the hCG sampling. The aim of this study is to establish a cutoff value of hCG as a predictor of a viable pregnancy, 10 days after performing a blastocyst ET. A cross-sectional, retrospective study was carried out in IVF cycles performed in our center between 2017 and 2018. Cycles included were fresh ET and frozen-thawed ET of blastocyst stage embryos that ended with a positive pregnancy test. Pregnancy was defined as a rise in hCG above 20 IU/L. All measurement of hCG levels were performed 10 days after the ET. A transvaginal ultrasound was performed on week 6 to confirm pregnancy. Pregnancies through preimplantation genetic test were excluded. A probable viable pregnancy was defined as a pregnancy greater than 12 weeks of gestational age, and a non-viable pregnancy as a positive hCG blood test with the consequent results: early miscarriage, biochemical pregnancy and ectopic pregnancy. Biochemical pregnancy was diagnosed if no sign of pregnancy was evident on ultrasound examination, miscarriage as pregnancy loss after ultrasonic visualization of a gestational sac. Ectopic pregnancies were diagnosed by transvaginal ultrasound. Results were not adjusted by multiple pregnancy. A level of statistical significance <5% was used. A total of 241 cases were included. Patients were classified according to their evolution in: Viable pregnancy: Pregnancy greater than 12 weeks of gestational age and pregnancy resulting in live birth. Non-viable pregnancy: Miscarriage, biochemical pregnancy and ectopic pregnancy. Out of the 241 cases, 161 patients presented viable pregnancies versus 80 patients with non-viable pregnancies; 43 miscarriages, 32 biochemical pregnancies, 5 ectopic pregnancies. An optimal hCG value was proposed as a predictor of pregnancy prognosis, comparing initial hCG values with the final outcome of the case. Cutoff values were proposed every 20 miU/mL from values of 80 mIU/mL up to 360 mIU/mL. For each value the Recall and the Precision were defined and graphed in a “PR” curve. The optimal cutoff value calculated, where the proportion of true positives is very high with respect to the amount of false positives, corresponds to 140 mIU/mL, statistically significant; p<0.0000. There was no statistical difference in hCG levels between fresh and frozen cycles. Considering that there is a statistically significant relationship between hCG values <140 miU/mL and non-viable pregnancies, an hCG value greater than or equal to 140 mIU/mL 10 days after performing a blastocyst stage ET can be used as a predictor of a pregnancy with a good prognosis during the first trimester, helping to better advice and monitor patients. Unless otherwise noted, all abstracts presented at ENDO are embargoed until the date and time of presentation. For oral presentations, the abstracts are embargoed until the session begins. Abstracts presented at a news conference are embargoed until the date and time of the news conference. The Endocrine Society reserves the right to lift the embargo on specific abstracts that are selected for promotion prior to or during ENDO.